Chemosensitivity enhanced by autophagy inhibition based on a polycationic nano-drug carrier. Issue 6 (10th February 2021) - Li, Na; Han, Shangcong; Ma, Baohua; Huang, Xia; Xu, Lisa; Cao, Jie; Sun, Yong
Abstract : With increasing understanding of the role of autophagy in tumorigenesis and development, studies have demonstrated that both excessive induction and inhibition of autophagy could improve the efficacy against tumors during cytotoxic or molecularly targeted drug therapy. Abstract : In recent years, with the increasing understanding of the role of autophagy in tumorigenesis and development, a steady stream of studies have demonstrated that both excessive induction and inhibition of autophagy could effectively improve the therapeutic efficacy against tumors during cytotoxic or molecularly targeted drug therapy. Among them, autophagy inhibition mediated by nanomaterials has become an appealing notion in nanomedicine therapeutics, since it can be exploited as an effective adjuvant in chemotherapy or as a potential anti-tumor agent. Herein, we constructed a pH-sensitive nanoplatform loaded with epirubicin (EPI) (mPEG- b -P(DPA- b -DMAEMA)/EPI), enabling effective autophagy inhibition in the process of tumor-targeting therapy and further sensitized the tumors to EPI. It was found that polycationic nanomicelles (PEDD-Ms) displayed specific localization in lysosomes after entering tumor cells and caused the impairment of lysosomal degradation capacity through lysosomal alkalization in a dose-dependent manner. HepG2 cells treated with PEDD-Ms displayed a large-scale accumulation of autophagosomes and LC3 (an autophagosome marker protein), and the degradation of the autophagy substrate p62 was also blocked, which indicated that these functional nanomicelles could significantly inhibit autophagy. Meanwhile, the typical morphological characteristics of autophagosomes were directly visualized by TEM. In vivo results also showed that the tumor-targeted and autophagy inhibition-associated nanoplatform therapy could effectively improve the therapeutic efficiency of EPI, which may be partially attributed to the fact that autophagy inhibition could enhance the sensitivity of tumor cells to EPI. Overall, we revealed the effect of polycationic nanomicelles on autophagic processes in tumor cells and explored their possible molecular mechanism, also considering the synergistic outcome between autophagy mediated by nanomaterials and chemotherapeutic drugs to improve the therapeutic effect on tumors.